Genomic insights into the adaptation to parasitism in nematode - trapping fungi and transcriptomics during infection of Caenorhabditis briggsae and plant-parasitic nematodes - KUMAR, DHARMENDRA (Indian Phytopathology, 2017)
Nematode-trapping fungi are a group of soil living microorganisms that form special adhesive and mechanical trapping structures to capture and kill the nematodes. Nematode- trapping fungi belong to a family Orbiliaceae of Phylum Ascomycota. Many plant parasitic nematodes species are destructive plant pathogens which resulted in an interest to use nematode-trapping fungi as bio control agents of plant parasitic nematodes. We used the comparative genomics and transcriptomics to gain insights in to the adaptation to parasitism in nematode-trapping fungi. We sequenced the genome of Monacrosporium haptotylum and compared with the genome of the adhesive net forming species Arthrobotrys oligospora. The genome assembly contains 40.4 million base pairs and 10959 genes. We found that two genomic mechanisms are likely to be involved in the evolution of parasitism in nematode- trapping fungi. First, gene duplications leading to formation of novel genes and expansion of gene families resulting in a large number of species – specific genes. Many of these genes were highly expressed and upregulated during infection of Caenorhabditis briggsae. Second, the differential gene expression of orthrologs between the two fungi during infection, suggest that the differential gene expression has been an important mechanisms for evolution of parasitism in nematode-trapping fungi. We also studied the transcriptome expressed by Arthrobotrys oligospora, Monacrosporium cionopagum and Arthrobotrys dactyloides during infection of root-knot nematode Meloidogyne hapla and sugar beet cyst nematode Heterodera schachtii. Comparative transcriptome analysis during infection process including trapping, penetration and digestion of Meloidogyne hapla and Heterodera schachtii by nematode-trapping fungi showed that the divergence in gene expression pattern associated with fungal species was significantly larger than that related to the host nematode species. Genes that were highly expressed in all nematode-trapping fungi encoded endopeptidases, such as peptisase_S8, peptidase_M3 and aspartic proteases; cell-surface proteins containing the carbohydrate-binding domain WSC; stress response proteins; membrane transporters; transcription factors; and cell singling genes containing the Ras domain. Transcripts containing the Ricin-B lectin and Atg8 domain were also highly expressed in all nematode- trapping fungi. Differentially expressed transcripts among the fungal species encoded various lectins, such as the fungal fruit-body lectin and the D-mannose binding lectin; transcription factors; cell-signaling components; proteins containing a WSC domain; and proteins containing a DUF3129 domain. Interestingly, DUF 3129 was highly expressed in M. cionopagum but not expressed at all in A. dactyloides. Differentially expressed transcripts during infection of different host nematodes, including peptidases, WSC domain proteins, tyrosinases, and small secreted proteins with unknown function.